Effect of viable cryopreserved human amniotic membrane sutured to cornea on course of experimental bacterial keratitis - K.V. Sereda; G.I. Drozhzhina; T.B. Gaidamaka; V.V. Vit; V.A. Shabliy; G. S. Lobyntseva (Ukrainian Society of Ophthalmologists, 2015)
Background: Since the human amniotic membrane (AM) has the features suggesting the potential for its use in the treatment of bacterial keratitis, and the efficacy of amniotic membrane transplantation for the disease is still poorly understood, the subject matter discussed in the paper is deemed to be relevant. Purpose: To investigate the anti-inflammatory effect of a viable cryopreserved human amniotic membrane (secured using various surgical techniques) in an in vivo model simulating bacterial keratitis. Materials and Methods: In 30 Chinchilla rabbits (30 eyes; weight, 2.5-3.0 kg), the transplantation of a viable amniotic membrane was performed for the previously developed model of moderate bacterial keratitis. The single layer graft inlay was used, and the amnion was secured to the cornea using eight interrupted 10-0 nylon sutures. Animals were followed up for one month. The control group included ten rabbits with experimental bacterial keratitis which received conventional medical therapy. Results: At day 30 after AMT, no lysis and partial lysis of the AM was found in 6/10 eyes and 4/10 eyes, respectively. No stromal edema, diffuse stromal edema, and mild stromal edema were found in 2 eyes, 2 eyes and 6 eyes, respectively. Spotty infiltration and the presence of neovascularization were revealed in 2 eyes and 4 eyes, respectively. Additionally, histology revealed complete epithelialization of the wound surface; however, lamellar differentiation of corneal epithelial cells was observed only in the central cornea. In some eyes, initial stromal neovascularization (especially in the superficial stromal lamellae and around the sutures) was noted. Conclusion: Since in bacteria-induced corneal damage of the same depth the biological covering technique results in a smaller amount of trauma and is accompanied by a lower inflammatory corneal response than those following the AM inlay grafting, the former technique should be preferred to the latter under these circumstances.